HEMOGLOBIN IN RELATION TO BODY MASS INDEX AND SOCIOECONOMIC CHARACTERISTICS AMONG PREGNANT WOMEN - Akram, Minal; Basharat, Shahnai; Qamar, Muhammad Mustafa; Basharat, Ayesha; Ahmed, Tanveer; Saleem, Sheraz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine whether the body mass index (BMI) and hemoglobin (HB) level are associated with socioeconomic strata among pregnant women belonging to different socioeconomic strata. Study Design: A cross-sectional study. Place and Duration of Study: Sheikh Zayed Hospital, National Hospital & Medical Center, and Hameed Latif Hospital Lahore (Punjab; Pakistan), from Mar to Dec 2018. Methodology: A cross-sectional study was conducted on 300 pregnant women of lower, middle and upper class; age range from 15-39 years. Women from all trimesters were included in the study. A self-structured questionnaire was used to collect socio-demographic data about participants of the study. Anthropometric measurements, body mass index (BMI), and hemoglobin (HB) level were evaluated in participants belonging to different socioeconomic status. Results: The study determined that 3% of participants were underweight, 29% had average weight, 45% belong to an overweight category, and 23% were obese as assessed based on BMI values. Hemoglobin level varied from 9.1 mg/dl to 11 mg/dl among participants of different socioeconomic strata. A significant association was observed between BMI, HB level, and socioeconomic status (p=0.000). However, there was no significant association observed between BMI and hemoglobin. Conclusion: It was concluded that the body mass index (BMI) and hemoglobin (HB) were significantly associated with socioeconomic conditions of pregnant women but showed no association with each other. This provided the potential for new avenues to improve health status during pregnancy.